EFEKTIVITAS EKSTRAK DAUN SERAI (Cymbopogon citratus) UNTUK PENGENDALIAN SERANGAN WERENG HIJAU PADA TANAMAN TERUNG - Kiky Nurfitri Sari; Andika Prawanto; Marzuki Rasyid; Meiyin Wildayana; Akbar Syahrin (PUCUK : Jurnal Ilmu Tanaman, 2022)
Green leafhopper is one of the important pests found in eggplant cultivation, especially in the Solanaceae family. To control the attack of green leafhoppers, in general, farmers will spray pesticides. This activity is an activity that aims to determine the effectiveness of lemongrass leaf extract for controlling green leafhopper attacks on eggplant plants tested. This activity was carried out at the Experimental Field of the Horticultural Crop Cultivation Study Program, Rejang Lebong State Community Academy. This activity was carried out from February to March 2022. In its implementation, this activity used an experimental design with a single Completely Randomized Design where each treatment was P0 (without spraying lemongrass leaf extract), P1 (Spraying Lemongrass Leaf Extract with a Concentration of 100 ml/ L), and P2 (Spraying Lemongrass Leaf Extract with a Concentration of 250 ml/L). the results of observations made it was known that there was a decrease in the population of green leafhoppers on plants after spraying treatment with lemongrass leaf extract. Although the analysis did not show a significantly different effect.